2015
DOI: 10.5943/mycosphere/6/2/5
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and species composition of arbuscular mycorrhizal fungi in Clerodendrum species

Abstract: Songachan LS, Kayang H, Moinao P 2015 -Diversity and species composition of arbuscular mycorrhizal fungi in Clerodendrum species. Mycosphere 6(2), 150-158, Doi 10.5943/mycosphere/6/2/5 AbstractTwo Clerodendrum species viz., Clerodendrum colebrookianum and Clerodendrum buchananii were studied for diversity of arbuscular mycorrhizal fungi (AMF). A rhizosphere soil was found to be acidic and soil phosphorus was low for both the plant species. AMF colonization in the form of arbuscules, vesicles and hyphae were ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…In this research we found that the species of Acaulospora were most common and predominant followed by Glomus, Sclerocystis, and Gigaspora. Our findings are further supported by the work of other researchers (Lovelock et al, 2003;Wongmo, 2008;Tchabi et al, 2008;Charoenpakdee et al, 2010;Gao and Guo, 2010;Songachan and Kayang, 2011) who investigated that there is higher number of Acaulospora in the soil followed by Glomus species. The predominance of Acaulospora species might be due to their adaptation to wide variety of soil types, host species and pH and nutrient availability etc ( Jefwa et al, 2006;Straker et al, 2010).…”
Section: Amf Speciessupporting
confidence: 91%
“…In this research we found that the species of Acaulospora were most common and predominant followed by Glomus, Sclerocystis, and Gigaspora. Our findings are further supported by the work of other researchers (Lovelock et al, 2003;Wongmo, 2008;Tchabi et al, 2008;Charoenpakdee et al, 2010;Gao and Guo, 2010;Songachan and Kayang, 2011) who investigated that there is higher number of Acaulospora in the soil followed by Glomus species. The predominance of Acaulospora species might be due to their adaptation to wide variety of soil types, host species and pH and nutrient availability etc ( Jefwa et al, 2006;Straker et al, 2010).…”
Section: Amf Speciessupporting
confidence: 91%
“…Likewise, Acaulospora species prefer acidic soils [39], and Gigaspora species are predominant in soil with high sand content [39]. The abundance of many types of AMF in India provided evidence that the genus Glomus is widespread across many environments, and there are several reports on the presence of Glomus in intensively managed agriculture systems [27,39,43,44]. Several agricultural practices, like the application of fertilizers, pesticides, tillage, etc., disturb the hyphal development of AMF and thus reduce the propagation of AMF spores [44].…”
Section: Discussionmentioning
confidence: 99%
“…The abundance of many types of AMF in India provided evidence that the genus Glomus is widespread across many environments, and there are several reports on the presence of Glomus in intensively managed agriculture systems [27,39,43,44]. Several agricultural practices, like the application of fertilizers, pesticides, tillage, etc., disturb the hyphal development of AMF and thus reduce the propagation of AMF spores [44]. AMF spores vary considerably from place to place according to the physical and chemical nature of the soil, and their distribution is influenced by several biotic and abiotic aspects [44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, OTU 499, belonging to the Phaeosphaeriaceae family, was enriched in intercropped Napier rhizospheres and is a monocotyledon-associated plant saprotroph or pathogen (Cannon and Kirk, 2007;Phookamsak et al, 2014). Lastly, Dentiscutata (OTU 828) in Napier is a known bene cial AMF genus that has been identi ed in acidic tropical agricultural soils, including India (Khade, 2010) and Brazil (Krüger et al, 2014).…”
Section: Intercropping Drives Changes In Rhizosphere Community Member...mentioning
confidence: 99%